Novel high stable electrocatalyst based on non-stoichiometric nanocrystalline niobium carbide toward effective hydrogen evolution. (10th May 2021) - Chebanenko, M.I.; Danilovich, D.P.; Lobinsky, A.A.; Popkov, V.I.; Rempel, A.A.; Valeeva, A.A.
Abstract: In this work, we have developed a method for the synthesis of non-stoichiometric nanocrystalline niobium carbide (NbCy ) using special heat treatment of niobium citrate in a vacuum. The powder synthesized was investigated by powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), high-resolution scanning electron microscopy (HRSEM), transmission electron microscopy (TEM), and low-temperature nitrogen sorption-desorption technique. The PXRD results showed that the synthesized niobium carbide nanocrystals had a cubic structure (space group F m-3m ), isometric morphology, and average crystallite size of about 12 nm. The Rietveld method was used to refine the unit cell parameters: a = b = c = 446.8 pm; Rwp = 5.48%. The specific surface area about 212 m 2 /g (BET) and the porosity about 0.02 cm 3 /g (BJH) of the sample were determined by adsorption-structural analysis; it was found that niobium carbide had a weakly pronounced microporous structure associated with the presence of interparticle porosity, which was also confirmed by the HRSEM results. The catalytic activity of non-stoichiometric niobium carbide in the process of electrolytic reforming of an aqueous ethanol solution was analyzed. The electrocatalyst has a low hydrogen overpotential value (−245 mV), a Taffel slope (90 mV/dec), and high operational stability: the absolute value of the overvoltage increases by 21 mV after 500 voltammetry cycles, and the current density decreases by 5% after 20 h of chronoamperometry. The results obtained make it possible to consider non-stoichiometric niobium carbide as a promising electrode base for electrocatalytic production of hydrogen from renewable aqueous-alcoholic solutions. Graphical abstract: Image 1 Highlights: Non-stoichiometric nano-NbCy was synthesized via thermolysis of niobium citrate. NbCy nanopowders are characterized by high surface area and hierarchical structure. Morphology features promote low OP of NbCy nanocrystals in ECR of ethanol. High stability of NbCy -based electrode possesses effective production of hydrogen.